2009
DOI: 10.1097/dad.0b013e3181a24b09
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Carcinosarcoma With Myoepithelial Differentiation: Immunohistochemical and Cytogenetic Analysis of a Case Presenting in an Unusual Location

Abstract: Primary cutaneous carcinosarcoma is an uncommon tumor that is characterized by an admixture of malignant epithelial and mesenchymal elements. To our knowledge, only approximately forty cases have been reported to date in the literature. The majority of these neoplasms occurred on the extremities and the head and neck region of older individuals. We report an additional case, which presented in an 87-year-old man in an unusual location, the buttock. Histologically, the lesion was characterized by a biphasic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The immunophenotypic studies performed in the reported cases are summarized in Table . Immunophenotypically, the basaloid epithelial component marks as expected, with immunoreactivity for cytokeratins, p63, bcl‐2, Ber‐EP4, variable EMA, and negative for mesenchymal and melanocytic markers.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The immunophenotypic studies performed in the reported cases are summarized in Table . Immunophenotypically, the basaloid epithelial component marks as expected, with immunoreactivity for cytokeratins, p63, bcl‐2, Ber‐EP4, variable EMA, and negative for mesenchymal and melanocytic markers.…”
Section: Discussionmentioning
confidence: 56%
“…Our case also showed coexpression of p16 and p63. Although p63 expression has been frequently reported in non‐cutaneous and squamous carcinosarcomas, it has been reported negative in all previous reports of basal cell carcinosarcomas . The coexpression of these three markers in both components supports the notion that they have a common origin.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…4 Histologically, the sarcomatous components of PCCS often are highly variable, with an absence of transitional areas within the epithelial component, which frequently resembles basal cell carcinoma and/ or SCC. [5][6][7] Primary cutaneous carcinosarcoma favors areas of chronic UV radiation exposure, particularly on the head and neck. Most tumors present with a slowly growing, polypoid, flesh-colored to erythematous nodule due to the infiltrative mesenchymal component.…”
Section: The Diagnosismentioning
confidence: 99%
“…The priority of long-term immunosuppression must be discussed critically. 42 In summary, division can be made into epithelial components (most commonly, BCCs and/or SCCs) and adnexal CS (benign/malignant spiradenomas, proliferating trichilemmal cystic carcinomas, or porocarcinomas).…”
Section: Characteristics Of Carcinosarcomas-lessons Learned From the mentioning
confidence: 99%